Moderate hypoxia influences excitability and blocks dendrotoxin sensitive K+ currents in rat primary sensory neurones - Henrich Michael; Stehr Annette; Ettorre Giovanni; Gruss Marco; Hempelmann Gunter; Scholz Andreas (SAGE Publishing, 2006)
Abstract Hypoxia alters neuronal function and can lead to neuronal injury or death especially in the central nervous system. But little is known about the effects of hypoxia in neurones of the peripheral nervous system (PNS), which survive longer hypoxic periods. Additionally, people have experienced unpleasant sensations during ischemia which are dedicated to changes in conduction properties or changes in excitability in the PNS. However, the underlying ionic conductances in dorsal root ganglion (DRG) neurones have not been investigated in detail. Therefore we investigated the influence of moderate hypoxia (27.0 ± 1.5 mmHg) on action potentials, excitability and ionic conductances of small neurones in a slice preparation of DRGs of young rats. The neurones responded within a few minutes non-uniformly to moderate hypoxia: changes of excitability could be assigned to decreased outward currents in most of the neurones (77%) whereas a smaller group (23%) displayed increased outward currents in Ringer solution. We were able to attribute most of the reduction in outward-current to a voltage-gated K+ current which activated at potentials positive to -50 mV and was sensitive to 50 nM α-dendrotoxin (DTX). Other toxins that inhibit subtypes of voltage gated K+ channels, such as margatoxin (MgTX), dendrotoxin-K (DTX-K), r-tityustoxin Kα (TsTX-K) and r-agitoxin (AgTX-2) failed to prevent the hypoxia induced reduction. Therefore we could not assign the hypoxia sensitive K+ current to one homomeric KV channel type in sensory neurones. Functionally this K+ current blockade might underlie the increased action potential (AP) duration in these neurones. Altogether these results, might explain the functional impairment of peripheral neurones under moderate hypoxia.